2017
DOI: 10.1525/elementa.234
|View full text |Cite
|
Sign up to set email alerts
|

Effective inundation of continental United States communities with 21st century sea level rise

Abstract: Recurrent, tidally driven coastal flooding is one of the most visible signs of sea level rise. Recent studies have shown that such flooding will become more frequent and extensive as sea level continues to rise, potentially altering the landscape and livability of coastal communities decades before sea level rise causes coastal land to be permanently inundated. In this study, we identify US communities that will face effective inundation—defined as having 10% or more of livable land area flooded at least 26 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…For the hurricane sample, a total of 608 respondents (152 respondents in each condition) who currently live in one of the hurricane-prone states identified by the NOAA [45,46] were recruited. For the flood sample, a total of 620 respondents (155 respondents in each condition) who currently live in one of the flood-prone states identified by the NOAA [47,48]. For earthquake sample, a total of 612 respondents (153 in each condition) who currently live in California were recruited.…”
Section: Respondentsmentioning
confidence: 99%
“…For the hurricane sample, a total of 608 respondents (152 respondents in each condition) who currently live in one of the hurricane-prone states identified by the NOAA [45,46] were recruited. For the flood sample, a total of 620 respondents (155 respondents in each condition) who currently live in one of the flood-prone states identified by the NOAA [47,48]. For earthquake sample, a total of 612 respondents (153 in each condition) who currently live in California were recruited.…”
Section: Respondentsmentioning
confidence: 99%
“…We would expect that the greater appearance of stormwater risks (e.g., areas that encompass a high percentage of impervious surfaces and that contain floodplain, or are located near coastal areas) would lead to higher plan quality score. With the direct threat from sea level rise, coastal areas in the United States are also at risk from chronic, disruptive flooding events which is defined as flooding that occurs 26 times per year or more [60,61]. More crucially, annual hurricane season poses greater potential impact on coastal communities rather than inland communities.…”
Section: Factors Influencing Plan Qualitymentioning
confidence: 99%
“…For large-area assessments (regional, continental, global), several choices are available for DEMs for the required topographic information to project potential impacts of increased coastal water levels, whether a simple inundation model is used or a more complex process-based or probabilistic model is employed. Previous research has demonstrated that the quality of data, and associated transformations, used for elevation-based assessments must be well understood and applied to properly model potential impacts (Gesch, 2009;Coveney and Fotheringham, 2011;Cooper et al, , 2015Gesch, 2013;Schmid et al, 2014;Dahl et al, 2017;Jones et al, 2017;West et al, 2018).…”
Section: Introductionmentioning
confidence: 99%